Pentingnya Pengelolaan Aspek Keuangan Perusahaan secara Efektif dan Efisien - Zainal Zainal (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
In the business and daily life world, the principle of management is essential to avoid the risk of disadvantage and become the main method to achieve financial goals. Management always discusses the principles of financial management and company management. The need for media such as financial reports analysis is to manage the company to be a reference and as a company’s reflection of its condition holistically. The main purpose of financial statements is to be a reference to measure the condition of the company. Is the company in a good condition or is there any disablement on the finance itself? Finance reports include a scale, income statement, the summary of retained earnings, and a statement of finance reports. While management is the art of how a manager manages the company. Broadly speaking, this financial management includes planning, organizing, leading, directing/Commanding, motivating, Coordinating, Controlling, Reporting, Staffing and Forecasting. A manager must understand well all these management functions. The better the managerial skill will be directly proportional to the significance of performance quality in the company